Revolusi Kampus, Wajah Baru Islam di Amerika - Musrifah, Musrifah (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
Israel's brutal attacks on Palestinian land continue. More than 35,000 Palestinian civilians have been killed. Most of the victims are women and children. The genocide committed by Israel and funded by the United States (US) has been condemned by the world. Interestingly, a massive wave of protests was carried out by students on prominent campuses in the US. This ally of Israel deployed a large number of police officers to stop student action. More than 1000 students from various campuses in the US were arrested by local police. However, the action did not stop and actually expanded to hundreds of campuses. The US student social movement confirms the theory of social movements led by youth and students, which is undeniable. The US student solidarity action has erupted into a campus revolution that places students as the main actors and agents of change. The campus revolution in the US has succeeded in giving a new color to US democracy that melts ideological barriers. The campus revolution in the US also presents a new face of Islam in the land of Pamansam, which is dominated by young people and scholars.